Independensi, Motivasi, Keahlian Profesional, Tingkat Pendidikan, Pengalaman Kerja dan Kinerja Pengawas Lembaga Perkreditan Desa - Sentosa, Komang Gede Arya Abdi; Budiartha, I Ketut (E-Jurnal Akuntansi; Vol 31 No 3 (2021), 2021)
The purpose of this study is to obtain empirical evidence related to the influence of Independence, Motivation, Professional Skills, Level of Education, and Work Experience on Internal Supervisor Performance. This research was conducted in 74 LPD in Klungkung Regency. The data analysis technique used is multiple linear regression. The results of this study indicate that Independence, Motivation, Professional Skills, Level of Education, and Work Experience have a positive and significant effect on the performance of internal supervisors. This shows the higher independence, motivation, professional expertise, education level, and work experience of a supervisor, the supervisor's performance will be better. For the LPD the results of this study can provide additional information related to factors that influence the performance of internal supervisors, so it is expected to be useful in improving the performance of LPD supervisors in Klungkung Regency. Keywords: Independence; Motivation; Professional Expertise; Level Of Education; Work Experience.